Determinan Tingkat Pengangguran Terbuka di Provinsi Banten Tahun 2008-2013 - Sunlip Wibisono; Jefti Sidania; Rafael Purtomo S (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
The purpose of this study was to determine of the effect of population, Gross Regional Domestic Product (GDP), and the Minimum Wages District (UMK) on the level of open unemployment rate in Banten Province. The data that used in this research was secondary data and data obtained Bps and relevance agencies. The analytical tool used in this research is panel data regression methods Fixed Effext Model (FEM). The object of this research is the district/city in Banten Province Period 2008-2013. The results of the research conducted is known that the number of populaton, GDP, and UMK significantly along the open unemployment rate in Banten Province. Keywords : Open unemployment rate, Population, GDP, and UMK